Factori asociați cu nașterea copiilor de rang diferit la femeile din Municipiul Chișinău - Grigoraș, Ecaterina (Calitatea Vieții, 2022)
The article presents the results of the sociological study on the reproductive behaviour of women in Chisinau. The purpose of the study is to highlight the socioeconomic situation of couples at the birth of children and the influence of some factors on the reproductive intention, in order to elucidate the characteristics of the reproductive behaviour of women in the municipality of Chisinau. The empirical basis of the study was the data of the quantitative sociological research carried out by the Centre for Demographic Research in 2019 on a sample of 600 women of reproductive age 18-40 years, who are married or cohabiting, with or without children. The situation of the respondents at the time of childbirth shows that many couples do not have enough living space, sufficient material sources, but also the lack of a stable job. The help from the parents is noted both in the education of the children and financially, especially at the birth of the first child. In the regression analysis, it was found that, for women from the municipality of Chisinau, demographic and economic factors have a significant impact on the probability of the intention to have a/ another child. For all women, the probability of intending to have children is decreasing with age and the number of children already born. Marital status is the predictor with the greatest impact on the likelihood of reproductive intention, followed by partner (employed) status, for women who have not yet given birth to any children, while insufficient income shows a decrease in the probability of the intention to have children. For women who have already given birth to a child, the availability of living space and the support of the parents, including the partner with financial resources, but also in raising and educating the child, increases the probability of the intention to have children give birth to another child.